PENGARUH MITOS PADA BENTUKAN RUANG BERMUKIM DI DESA NGADAS KECAMATAN PONCOKUSUMO KABUPATEN MALANG (Myth Effect on Living Space Formation at Ngadas of Pondokusumo Sub-District, Malang District) - Maria Christina Endarwati (Universitas Katolik Soegijapranata, 2013)
ABSTRACT A myth is an event in the past of a certain region or area that was believed mystical or supernatural. A myth is also believed to greatly affect people's lives in terms of their belief system so that it arises rules and rituals that are then performed by the people of the region. Until now many people remain using mystical values as bases affecting the living space concepts. However, a myth could possibly change together with the changes of the societal values. This research took the case of the people of Tengger at Ngadas rural area of Malang District which remained embracing their original belief system named Budho Tengger. This belief said that the land around was holy and thus it affected the community to maintain and preserve the surrounding environment. The people were not allowed to carelessly cut the trees down because such an act was believed fatalistic to those conducting. Of the myth a typical space formation of living space arouses. This study used qualitative research method, meaning to analyze the existing myth based on the people's characteristics and to analyze the occurring space formation. Based on the study results is could be concluded that the characteristics of Ngadas community were still traditional and were highly influenced by the myth passing from one generation to the other generations. In addition, there were traditional rules and beliefs of Tengger people that affected their living space formation, namely the sacred space and the profane space. Keywords: living space formation, myth, Tengger tribe. ABSTRAK Mitos adalah peristiwa dalam suatu daerah pada masa lampau yang bersifat mistis atau gaib dan diyakini dapat sangat mempengaruhi kehidupan masyarakat dalam hal kepercayaan, sehingga timbul aturan-aturan dan ritual-ritual yang dilakukan oleh masyarakat dari suatu daerah. Hingga saat ini sebagian masyarakat masih menggunakan nilai-nilai mistis sebagai landasan yang dapat mempengaruhi konsep ruang bermukim. Namun mitos ini dapat mengalami perubahan sesuai dengan perubahan nilai-nilai yang dianut masyarakatnya. Penelitian ini mengambil kasus pada suku masyarakat Tengger di Desa Ngadas, Kabupaten Malang yang masih menganut kepercayaan asli (Budho Tengger) yang berkeyakinan bahwa tanah di sekitar adalah suci sehingga mempengaruhi masyarakat untuk menjaga dan melestarikan lingkungan disekitarnya dengan tidak menebang pohon sembarangan karena diyakini akan berakibat fatal bagi yang melakukannya. Dari mitos tersebut ternyata juga menimbulkan suatu bentukan ruang khas di dalam ruang bermukim.